Synthesis of novel psoralen analogues and their in vitro antitumor activity - Francisco, Carla Santana (2013)
New tetracyclic benzofurocoumarin (benzopsoralen) analogues were synthesized and their inhibitory effect on the growth of tumor cell lines was evaluated. The human tumor cell lines used were MDA MB231 (breast adenocarcinoma), HeLa (cervix adenocarcinoma) and TCC-SUP (bladder transitional cell carcinoma). The in vitro antitumor activity of the new benzopsoralens was discussed in terms of structure–activity relationship. Molecular docking studies with human-CYP2A6 enzymes were also carried out with the synthesized compounds in order to evaluate the potential of these compounds to interact with the heme group of the enzymes. The results have demonstrated that the linear compounds have the most pronounced activity against tumor cell lines and this might be related to the better accessibility that these compounds have to the active site in relation to the angular ones that have shown in the majority of the cases multiple binding poses in the active site of CYP2A6.